THE INFLUENCE OF FARMER ABILITY AND FARMER MOTIVATION ON INCOME OF LARGE RED CHILI FARMING BUSINESS IN CIBEUREUM VILLAGE, SUKAMANTRI DISTRICT, CIAMIS REGENCY - Agustian, Andri; Nuraini, Candra; Atmaja, Unang (Universitas Veteran Bangun Nusantara, 2025)
This research aims to (1) the level of ability of large red chili farmers (2) the level of motivation of large red chili farmers (3) the level of income from large red chili farming (4) Analyzing the influence of farmer ability and farmer motivation on farming income in Cibeureum Village, Sukamantri District, Regency Ciamis. Data collection in this research used a survey method carried out in Cibeureum Village, Sukamantri District, Ciamis Regency. The number of respondents in this study was 32 respondents. The analysis in this research uses descriptive analysis and multiple linear regression analysis. The research results show that the level of farmers' ability to earn income is categorized as high. The level of motivation of farmers regarding farming income in Cibeureum Village, Sukamantri District, Ciamis Regency is categorized as high. The income level of large red chili farming is categorized as high. Farmers' abilities and farmers' motivation influence the income of large red chili farming in Cibeureum Village, Sukamantri District, Ciamis Regency. The Adjust R Square results show that farmer ability and farmer motivation have an influence of 69.30 percent on farming income.